2016
DOI: 10.1038/ncomms13573
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the RBM7–ZCCHC8 core of the NEXT complex reveals connections to splicing factors

Abstract: The eukaryotic RNA exosome participates extensively in RNA processing and degradation. In human cells, three accessory factors (RBM7, ZCCHC8 and hMTR4) interact to form the nuclear exosome targeting (NEXT) complex, which directs a subset of non-coding RNAs for exosomal degradation. Here we elucidate how RBM7 is incorporated in the NEXT complex. We identify a proline-rich segment of ZCCHC8 as the interaction site for the RNA-recognition motif (RRM) of RBM7 and present the crystal structure of the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 55 publications
(83 reference statements)
2
50
0
Order By: Relevance
“…Our interface is similar to that recently observed in the RBM7-ZCCHC8 structure ( Fig. 3; Falk et al 2016). It was suggested that the mutually exclusive interaction of RBM7 with ZCCHC8 and SAP145…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our interface is similar to that recently observed in the RBM7-ZCCHC8 structure ( Fig. 3; Falk et al 2016). It was suggested that the mutually exclusive interaction of RBM7 with ZCCHC8 and SAP145…”
Section: Discussionsupporting
confidence: 91%
“…Apart from the conserved tryptophan, our structure lacks the other important UHM-ULM features. Instead, it represents a recently discovered novel type of RRM protein interaction (Falk et al 2016). In our structure an extensive and conserved hydrophobic interface is present.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The NEXT complex promotes degradation of PROMPTs and 3 ′ extended RNAs, including aberrant hTR, in the nucleoplasm (Preker et al 2008;Lubas et al 2011;Tseng et al 2015). A recent study showed that ZCCHC8 interacts with the RNA recognition motif (RRM) domain of RBM7 via a proline-rich sequence and bridges interactions with MTR4 in the complex (Falk et al 2016). PAXT promotes degradation of longer and more mature [with respect to poly(A) tail length] substrates compared with NEXT substrates (Meola et al 2016).…”
Section: Cofactor-mediated Bridging To the Cap-binding Complexmentioning
confidence: 99%
“…In addition, the RBM7 RRM contains a proline-rich region that not only directly interacts with ZCCHC8 ( Fig. 3B), but also, in a mutually exclusive manner, binds to SAP145, a spliceosomal SF3b complex component, providing a potential mechanism for how the NEXT complex recognizes intronic RNAs (Falk et al 2016).…”
Section: Exosome Cofactor Gene Mutations Rbm7mentioning
confidence: 99%